TANGGUNG JAWAB SOSIAL KORPORAT TERHADAP PEKERJA DAN KINERJA EKONOMI : SATU TINJAUAN - Dina Madinah; Mara Ridhuan Che Abdul Rahman; Shifa Mohd Nor; Mohd Rizal Palil (FEB Universitas Sultan Ageng Tirtayasa, 2018)
Corporate social responsibility is carried out by the company to pay attention to and fulfill the stakeholders' needs. This is done by the company to get support from stakeholders. Workers are one of the important stakeholders for the company because workers are involved in the company's operational activities in an effort to achieve the company's economic performance. Therefore, it is very important for the company to carry out corporate social responsibility towards workers. This research will examine the corporate social responsibility to workers and their influence on the company's economic performance. Some of the implementation of corporate social responsibility towards workers has proven to have a significant influence on the economic performance of the company including giving high salaries to workers, paying attention to the health and safety of workers, providing education and training, fostering good relations among workers, providing pensions and providing equal opportunities to every worker. Based on a review and analysis of previous research, to get more information about the practice of corporate social responsibility towards workers, this study reserved for further research that focuses its research on corporate social responsibility towards workers and examines the possibility of other factors that can confirm the relationship between corporate social responsibility for workers with economic performance.